2014
DOI: 10.1016/j.ecss.2014.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns of nature-based tourism interactions with whale sharks (Rhincodon typus) at Ningaloo Reef, Western Australia

Abstract: a b s t r a c tAs with other nature-based tourism ventures, whale shark tourism is expanding rapidly worldwide, which highlights the need to understand more about the nature of these activities. Records of interactions between tour operators and whale sharks at Ningaloo Reef, Western Australia (22. (2009 and 2010) were used to plot the smoothed densities of tour operator interactions with whale sharks. Generalised linear models were used to investigate how the presence/absence and number of whale shark inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
12
0
1
Order By: Relevance
“…The correlation between ENSO and the LC strength affects species biology and ecology within WA waters. For example, La Niña events have positive impacts on growth rates of fish (Nguyen et al., ; Ong et al., ) and corals (Ong et al., ) and altered the distribution patterns of aggregating whale sharks ( Rhincodon typus ; Anderson et al., ; Wilson, Taylor, & Pearce, ). During the strong La Niña event in summer 2011, there was an extreme warming of SST with anomalies of 2–4 ° C persisting for several months (Pearce & Feng, ), during which ecosystems and marine species were affected (Feng, McPhaden, Xie, & Hafner, ; Smale & Wernberg, ; Wernberg et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between ENSO and the LC strength affects species biology and ecology within WA waters. For example, La Niña events have positive impacts on growth rates of fish (Nguyen et al., ; Ong et al., ) and corals (Ong et al., ) and altered the distribution patterns of aggregating whale sharks ( Rhincodon typus ; Anderson et al., ; Wilson, Taylor, & Pearce, ). During the strong La Niña event in summer 2011, there was an extreme warming of SST with anomalies of 2–4 ° C persisting for several months (Pearce & Feng, ), during which ecosystems and marine species were affected (Feng, McPhaden, Xie, & Hafner, ; Smale & Wernberg, ; Wernberg et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This study, the most extensive satellite telemetry study on R. typus conducted in Australia, has shown that sharks generally made relatively short forays away from Ningaloo Reef before returning to the area intra‐annually (Figure ). Previous studies have suggested that sharks exhibit high individual fidelity to the Ningaloo Reef area during the austral autumn/winter, with individuals often resighted in the area over consecutive years (Anderson et al., ; Holmberg, Norman, & Arzoumanian, ; Holmberg et al., ; Norman & Morgan, ; Norman et al., ). While these observations documented the usage by R. typus of areas accessed by tourism operators during the whale shark season, the movements and whereabouts of sharks between these resighting events remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The whale shark ecotourism industry at Ningaloo Reef operates during the “whale shark season,” that is, the period during which whale sharks are known to aggregate at Ningaloo Reef. This is during the austral autumn and winter, generally between March and July (Anderson et al., ; Government of Western Australia Department of Parks and Wildlife, ; Holmberg, Norman, & Arzoumanian, ), sometimes extending into August and September (Government of Western Australia Department of Parks and Wildlife, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations